Activation in human auditory cortex in relation to the loudness and unpleasantness of low-frequency and infrasound stimuli - Behler, Oliver (PLoS One, 2020)
Low frequency noise (LFS) and infrasound (IS) are controversially discussed as potential causes of annoyance and distress experienced by many people. However, the perception mechanisms for IS in the human auditory system are not completely understood yet. In the present study, sinusoids at 32 Hz (at the lower limit of melodic pitch for tonal stimulation), as well as 8 Hz (IS range) were presented to a group of 20 normal hearing subjects, using monaural stimulation via a loudspeaker sound source coupled to the ear canal by a long silicone rubber tube. Each participant attended two experimental sessions. In the first session, participants performed a categorical loudness scaling procedure as well as an unpleasantness rating task in a sound booth. In the second session, the loudness scaling procedure was repeated while brain activation was measured using functional magnetic resonance imaging (fMRI). Subsequently, activation data were collected for the respective stimuli presented at fixed levels adjusted to the individual loudness judgments. Silent trials were included as a baseline condition. Our results indicate that the brain regions involved in processing LFS and IS are similar to those for sounds in the typical audio frequency range, i.e., mainly primary and secondary auditory cortex (AC). In spite of large variation across listeners with respect to judgments of loudness and unpleasantness, neural correlates of these interindividual differences could not yet be identified. Still, for individual listeners, fMRI activation in the AC was more closely related to individual perception than to the physical stimulus level.